P899 Analysis of IL-23 receptor genetic variants associations with gut microbiome composition and barrier function in a cohort of healthy first-degree relatives of subjects with Crohn's disease. (30th January 2023) - Leibovitzh, H; Neustaeter, A; Lee, S H; Xue, M; Espin-Garcia, O; Olivera, P A; Mbareche, H; Huynh, H Q; Griffiths, A M; Turner, D; Madsen, K L; Silverberg, M S; et al.
Abstract: Background: Single nucleotide polymorphisms (SNPs) in the Interleukin 23 receptor (IL23R ) gene have been implicated in CD pathogenesis and shown in animal models to be involved in regulation of intestinal epithelial barrier function via the production of IL17A. Additionally, previous studies suggest that IL23R may impact gut microbial composition potentially via impairment of microbial clearance. Therefore, we hypothesized that IL23R risk alleles might be associated with altered gut barrier function and gut microbial composition in humans. Methods: The Genetic Environmental Microbial (GEM) project recruited a cohort of healthy first-degree relatives (FDRs) of patients with CD. Genotypic data (Illumina HumanCoreExome chip, immunochip or Human Global Screen Array) was available for 2, 716 subjects after imputation (Michigan sever). A weighted IL23R genetic risk score (IL23R-GRS) was generated based on 18 IL23R SNPs reported to be associated with susceptibility for CD (PMID: 26678098). The score was dichotomized as Quantile 5 (high IL23R-GRS) versus Quantiles 1-4 (low IL23R-GRS). A subset of this cohort was characterized for urinary fractional excretion of lactulose to mannitol ratio (LMR) to assess gut barrier function (N=1, 718), and fecal 16s rDNA gene sequencing (MiSeq) for microbiome profiling (N= 2, 638). Dichotomized LMR at a threshold of 0.025 was considered as abnormal. Linear and logistic regression models were used to assess associations of GRS with the LMR and microbial taxa. All models were adjusted for age, gender and five genetic principal components. Results: The median age of the cohort was 17 [Interquartile range 12-25] years and 53.9% were females. There were no differences in the proportion of baseline abnormal LMR>0.025 among subjects with high vs. low IL23R-GRS (20.7% vs. 21.4%, respectively; p=0.84). High IL23R-GRS was not associated with either LMR (b-coefficient=-0.0012, SE=0.0013, p=0.32) or dichotomized LMR>0.025 (b-coefficient=-0.052, SE=0.15, p=0.73). Additionally, although high IL23R-GRS was not associated with differences in microbial alpha diversity (Shannon index, p=0.08), it showed modest compositional shifts (Bray Curtis index, PERMANOVA: R 2 =0.001, p=0.002) and a trend with nine genera differential abundances (including a decrease in Faecalibacterium and Lachnospiraceae_NK4A136_group and an increase in Alistipes and Akkermansia ; false discovery rate of q<0.1 for all). Conclusion: The IL23R-GRS was not associated with abnormal gut barrier function but showed associations with microbial community composition and trends with individual genera. Further studies are required to understand if the effect of IL23R genetic variants on the risk of CD onset is mediated by the gut microbiome or other biological risk factors.